Improving English Vocabulary of Grade VIII Students Through Code Mixing at Junior High School - Dina Navisa D. Agusalim; Abdul Kamaruddin; Wahyudin; Mawardin M. Said (Institut Agama Islam Negeri Palopo, 2025)
The objective of the research is to ensure whether or not employing code mixing can improve English vocabulary of grade VIII students at SMP Negeri 15 Palu. The population of this research was the eighth grade students at SMP Negeri 15 Palu. Researcher selected sample using purposive sampling technique. The sample of this study were students of class VIII B as an experimental class totaling 31 students and class VIII C as a control class totaling 33 students. The data were analyzed statistically to determine the significant difference of students achievement in pre-test and post-test. The mean score of the experimental class on the pretest was 42.19 and the control class was 43.39. Th mean score of the experimental class on posttest was 78.70 and control class was 44.72. By using 0.05 level of significance and 62 degree of freedom, the researcher get the result t-counted (9.11) was higher than t-table (1.657). It means that the hypothesis is accepted. In conclusion, the use of code mixing can improve English vocabulary of grade VIII students at SMP Negeri 15 Palu.